2013
DOI: 10.1007/s00414-013-0870-3
|View full text |Cite
|
Sign up to set email alerts
|

Preliminary results on the postmortem measurement of 3-beta-hydroxybutyrate in liver homogenates

Abstract: The concentrations of 3-beta-hydroxybutyrate (3HB) in blood and two liver samples were retrospectively examined in a series of medicolegal autopsies. These cases included diabetic ketoacidosis, nondiabetic individuals presenting moderate to severe decompositional changes and nondiabetic medicolegal cases privy of decompositional changes. 3HB concentrations in liver sample homogenates correlate well with blood values in all examined groups. Additionally, decompositional changes were not associated with increase… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 50 publications
0
5
0
Order By: Relevance
“…Beta-hydroxybutyrate concentrations in liver homogenates correlated well with blood values in both diabetic and non-diabetic patients and were not influenced by time after death, thus allowing diabetic ketoacidosis to be diagnosed. Analogously, blood and synovial fluid beta-hydroxybutyrate concentrations were correlated with increased blood levels reflected in increased synovial fluid concentrations ( 76 , 77 ).…”
Section: Acetone Acetoacetate and Beta-hydroxybutyratementioning
confidence: 90%
See 1 more Smart Citation
“…Beta-hydroxybutyrate concentrations in liver homogenates correlated well with blood values in both diabetic and non-diabetic patients and were not influenced by time after death, thus allowing diabetic ketoacidosis to be diagnosed. Analogously, blood and synovial fluid beta-hydroxybutyrate concentrations were correlated with increased blood levels reflected in increased synovial fluid concentrations ( 76 , 77 ).…”
Section: Acetone Acetoacetate and Beta-hydroxybutyratementioning
confidence: 90%
“…Interesting results were obtained by Palmiere et al ( 76 , 77 ), who measured beta-hydroxybutyrate levels in liver homogenates and synovial fluid. Beta-hydroxybutyrate concentrations in liver homogenates correlated well with blood values in both diabetic and non-diabetic patients and were not influenced by time after death, thus allowing diabetic ketoacidosis to be diagnosed.…”
Section: Acetone Acetoacetate and Beta-hydroxybutyratementioning
confidence: 96%
“…Furthermore, blood β-hydroxybutyrate levels in decomposed bodies can be considered an appropriate biochemical parameter in the estimation of β-hydroxybutyrate concentrations at the time of death. Indeed, β-hydroxybutyrate concentration does not increase after death and may, at most, decrease as a result of spontaneous molecule degradation [41][42][43].…”
Section: Postmortem Biochemistrymentioning
confidence: 99%
“…Recent studies have indicated that β-hydroxybutyrate can be reliably measured in liver homogenates and may prove useful in confirming the presence of metabolic disturbances at the time of death. Liver homogenates can therefore be considered an alternative biological sample for βhydroxybutyrate determination; limited amounts of biological fluids must be reserved for toxicology and biochemical analyses [43].…”
Section: Postmortem Biochemistrymentioning
confidence: 99%
“…Within a long postmortem delay and thus taphonomic processes, there is a disappearance of blood, vitreous humor and pericardial fluid though the liver persists. In this context, Palmiere et al [52] published preliminary but promising results in 2013 regarding the exploration of HB in "liver homogenates". In the future, pathologies with hyperketonemia, in our case hypothermia, could be explored despite long postmortem intervals.…”
Section: Ketones Bodiesmentioning
confidence: 99%